The effect of nurse practitioner (NP-led) care on health-related quality of life in people with multiple sclerosis – a randomized trial - Penelope Smyth; Kaitlyn E. Watson; Yazid N. Al Hamarneh; Ross T. Tsuyuki (BMC Neurology, 2022)
Abstract Background Care for People with Multiple Sclerosis (PwMS) is increasingly complex, requiring innovations in care. Canada has high rates of MS; it is challenging for general neurologists to optimally care for PwMS with busy office practices. The aim of this study was to evaluate the effects of add-on Nurse Practitioner (NP)-led care for PwMS on depression and anxiety (Hospital Anxiety and Depression Scale, HADS), compared to usual care (community neurologist, family physician). Methods PwMS followed by community neurologists were randomized to add-on NP-led or Usual care for 6 months. Primary outcome was the change in HADS at 3 months. Secondary outcomes were HADS (6 months), EQ5D, MSIF, CAREQOL-MS, at 3 and 6 months, and Consultant Satisfaction Survey (6 months). Results We recruited 248 participants; 228 completed the trial (NP-led care arm n = 120, Usual care arm n = 108). There were no significant baseline differences between groups. Study subjects were highly educated (71.05%), working full-time (41.23%), living independently (68.86%), with mean age of 47.32 (11.09), mean EDSS 2.53 (SD 2.06), mean duration since MS diagnosis 12.18 years (SD 8.82) and 85% had relapsing remitting MS. Mean change in HADS depression (3 months) was: -0.41 (SD 2.81) NP-led care group vs 1.11 (2.98) Usual care group p = 0.001, sustained at 6 months; for anxiety, − 0.32 (2.73) NP-led care group vs 0.42 (2.82) Usual care group, p = 0.059. Other secondary outcomes were not significantly different. There was no difference in satisfaction of care in the NP-led care arm (63.83 (5.63)) vs Usual care (62.82 (5.45)), p = 0.194). Conclusion Add-on NP-led care improved depression compared to usual neurologist care and 3 and 6 months in PwMS, and there was no difference in satisfaction with care. Further research is needed to explore how NPs could enrich care provided for PwMS in healthcare settings. Trial registration Retrospectively registered on clinicaltrials.gov ( ClinicalTrials.gov Identifier: NCT04388592 , 14/05/2020).